A Consumption Orientation to Motherhood in Hong Kong - Adams, Jacqueline (2010)
What having a child means to women who anticipate having a child without the assistance of reproductive technology is an understudied subject, particularly in the Chinese context. In Hong Kong, women who do not yet have a child think of the enterprise as costly in terms of money, freedom, and time, requiring preparedness, and conferring positive experiences including the status of 'complete family,' being cared for in old age, and the ownership of something' cute.' They approach the decision in a highly rational manner, as one would an important purchase. They face it, in other words, with a consumption orientation. These findings emerge from the analysis of twenty-six in- depth, semi-structured interviews with Hong Kong Chinese would-be mothers.